The Intensity-Modulated Pelvic Node and Bladder Radiotherapy (IMPART) Trial: A Phase II Single-Centre Prospective Study. Issue 2 (February 2020) - Tan, M.P.; Harris, V.; Warren-Oseni, K.; McDonald, F.; McNair, H.; Taylor, H.; Hansen, V.; Sharabiani, M.; Thomas, K.; Jones, K.; Dearnaley, D.; Hafeez, S.; et al.
Abstract: Aims: Node-positive bladder cancer (NPBC) carries a poor prognosis and has traditionally been treated palliatively. However, surgical series suggest that a subset of NPBC patients can achieve long-term control after cystectomy and lymph node dissection. There is little published data regarding the use of radiotherapy to treat NPBC patients. This is in part due to concerns regarding the toxicity of whole-pelvis radiotherapy using conventional techniques. We hypothesised that, using intensity-modulated radiotherapy (IMRT), the pelvic nodes and bladder could be treated within a radical treatment volume with acceptable toxicity profiles. Materials and methods: The Intensity-modulated Pelvic Node and Bladder Radiotherapy (IMPART) trial was a phase II single-centre prospective study designed to assess the feasibility of delivering IMRT to treat the bladder and pelvic nodes in patients with node-positive or high-risk node-negative bladder cancer (NNBC). The primary end point was meeting predetermined dose constraints. Secondary end points included acute and late toxicity, pelvic relapse-free survival and overall survival. Results: In total, 38 patients were recruited and treated between June 2009 and November 2012; 22/38 (58%) had NPBC; 31/38 (81.6%) received neoadjuvant chemotherapy; 18/38 (47%) received concurrent chemotherapy; 37/38 (97%) patients had radiotherapy planned as per protocol. Grade 3 gastrointestinal and genitourinary acute toxicity rates were 5.4 and 20.6%, respectively. At 1 year, the grade 3 late toxicity rate was 5%; 1-, 2- and 5-year pelvic relapse-free survival rates were 55, 37 and 26%, respectively. The median overall survival was 1.9 years (95% confidence interval 1.1–3.8) with 1-, 2- and 5-year overall survival rates of 68, 50 and 34%, respectively. Conclusion: Delivering IMRT to the bladder and pelvic nodes in NPBC and high-risk NNBC is feasible, with low toxicity and low pelvic nodal recurrence rates. Long-term control seems to be achievable in a subset of patients. However, relapse patterns suggest that strategies targeting both local recurrence and the development of distant metastases are required to improve patient outcomes. Highlights: Radical IMRT to the bladder and pelvic nodes is feasible with low toxicity rates. A subset of node-positive bladder cancer patients attain disease control with IMRT. Relapse patterns suggest optimisation of local and systemic treatments is needed.